-x+1=2x+13

Simple and best practice solution for -x+1=2x+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x+1=2x+13 equation:


Simplifying
-1x + 1 = 2x + 13

Reorder the terms:
1 + -1x = 2x + 13

Reorder the terms:
1 + -1x = 13 + 2x

Solving
1 + -1x = 13 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
1 + -1x + -2x = 13 + 2x + -2x

Combine like terms: -1x + -2x = -3x
1 + -3x = 13 + 2x + -2x

Combine like terms: 2x + -2x = 0
1 + -3x = 13 + 0
1 + -3x = 13

Add '-1' to each side of the equation.
1 + -1 + -3x = 13 + -1

Combine like terms: 1 + -1 = 0
0 + -3x = 13 + -1
-3x = 13 + -1

Combine like terms: 13 + -1 = 12
-3x = 12

Divide each side by '-3'.
x = -4

Simplifying
x = -4

See similar equations:

| -3x-25+15x=8+15 | | -10(v+3)=-25 | | 3(r+4)-6r=-9(-3) | | -2x^2m^2(m^2-4m)= | | x+102=4x | | -7+n=3n+1 | | 75h+10= | | 15+1.50x=45 | | 14=n+8+5n | | 10x-50=-15 | | 1-5v-7v=-11 | | -9-8n=8(-6n+3)+7n | | 15x-50-5x=-15 | | -5x=54 | | 12-5=42 | | 8x-5x=8+3x+6 | | (x+102)=4x | | -24=6(-b-6) | | 59.95=11.99x | | =7x-11y+5x-3y+14-3 | | 7x-5=17-4x | | 39.95+0.45x=59.95+0.35x | | 35m+31=20m-74 | | x+50+80+60=180 | | 6x-22=x+32 | | =8(2x-5)+4x+30 | | x+51+48+90=180 | | 25m+94=-8m+28 | | Sin(4x)+sin(8x)=o | | 2z=6z-8 | | -5x+15=-8x+21 | | 4x+6+80+50=180 |

Equations solver categories